Echocardiographic detection of cardiac ectopy: a possible alternative to electrophysiological mapping? - Bara, Christoph Leon; Niehaus, Michael; Ghodsizad, Ali; Akhyari, Payam; Karck, Matthias; Ruhparwar, Arjang (The heart surgery forum, 2010)
PURPOSE: Three-dimensional (3-D) visualization of ventricular activation sequence is imperative for the diagnosis and treatment of malignant cardiac arrhythmias. Modern mapping systems that serve as the gold standard for detection and localization of the focus are costly and require an invasive approach into the cavity of the ventricles. The aim of our study was the development of a noninvasive and 3-D mapping system based upon echocardiography. - METHODS: In a porcine model, animals underwent ablation of the atrioventricular node (AV-node). 3-D electrophysiological cardiac mapping was performed using the ENSITE™ electro-anatomical system (St. Jude Medical, Minneapolis, MN, USA). Simultaneously, transesophageal echocardiography (TEE) including pulse wave (Pw) tissue Doppler was performed, and time to peak early diastolic velocity (PEDV) was measured. Both ENSITE-mapping and tissue Pw-Doppler were compared as to their ability to pinpoint the origin of ventricular ectopic focus. - RESULTS: PEDV corresponded well with the results as determined by noncontact mapping with ENSITE. - CONCLUSIONS: Tissue Doppler is a reliable method to deliver information about the topography of first onset of myocardial excitation. Further development of this method with a higher regional resolution and integration of color Doppler as well as 3-D echocardiography may eventually lead to the development of a completely noninvasive and echo-based electromechanical mapping system.
Gesehen am 30.11.2022